Metabolism, hypoxia and the diabetic heart - Heather, L; Clarke, K (2011)
The diabetic heart becomes metabolically remodelled as a consequence of exposure to abnormal circulating substrates and hormones. Fatty acid uptake and metabolism are increased in the type 2 diabetic heart, resulting in accumulation of intracellular lipid intermediates and an increased contribution of fatty acids towards energy generation. Cardiac glucose uptake and oxidation are decreased, predominantly due to increased fatty acid metabolism, which suppresses glucose utilisation via the Randle cycle. These metabolic changes decrease cardiac efficiency and energetics in both humans and animal models of diabetes. Diabetic hearts have decreased recovery following ischemia, indicating a reduced tolerance to oxygen-limited conditions. There is evidence that diabetic hearts have a compromised hypoxia signalling pathway, as hypoxia-inducible factor (HIF) and downstream signalling from HIF are reduced following ischemia. Failure to activate HIF under oxygen-limited conditions results in less angiogenesis, and an inability to upregulate glycolytic ATP generation. Given that glycolysis is already suppressed in the diabetic heart under normoxic conditions, the inability to upregulate glycolysis in response to hypoxia may have deleterious effects on ATP production. Thus, impaired HIF signalling may contribute to metabolic and energetic abnormalities, and impaired collateral vessel development following myocardial infarction in the type 2 diabetic heart. © 2011 Elsevier Ltd.